2015
DOI: 10.14245/kjs.2015.12.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Painless Foot Drop due to Cerebral Infarction Mimicking Lumbar Radiculopathy: A Case Report

Abstract: Although they usually originate from peripheral problems, foot drop is caused by lesions affecting the neural pathway related to dorsiflexor muscles, whether of central or peripheral origin. We present a patient with sudden isolated foot drop caused by a small infarct in the primary motor cortex mimicking a peripheral origin. This report indicates that patients presenting isolated foot drop should be managed carefully and the possibility of both central and peripheral causes should be considered. To our knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…These authors encouraged awareness of patients who have both a peripheral lesion in the lumbar spine and a central lesion in the primary motor cortex, as the UMN lesion was masked by the LMN lesion. 8 These previous cases are similar to our case 3 with the concurrent lumbar spinal pathology and a UMN lesion. All of these cases underwent unnecessary spinal surgical procedures (lumbar in 2 cases and cervical facet biopsy in 1 case) before the definitive cause of the SFD was diagnosed, that is, a meningioma in 2 cases and cerebral infarction in the other.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These authors encouraged awareness of patients who have both a peripheral lesion in the lumbar spine and a central lesion in the primary motor cortex, as the UMN lesion was masked by the LMN lesion. 8 These previous cases are similar to our case 3 with the concurrent lumbar spinal pathology and a UMN lesion. All of these cases underwent unnecessary spinal surgical procedures (lumbar in 2 cases and cervical facet biopsy in 1 case) before the definitive cause of the SFD was diagnosed, that is, a meningioma in 2 cases and cerebral infarction in the other.…”
Section: Discussionsupporting
confidence: 88%
“… 4 They stressed that the diagnosis of the central cause of foot drop may be delayed and that patients may undergo needless surgeries. Kim et al 8 reported a case of a patient with complaints of weakness of the left foot with a normal physical examination. Lumbar MRI showed a ruptured disc with compression of the left L4–5 nerve root.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations